Apprenticeship Learning and Adolescents’ Acquisition of Social and Cognitive Skills in Tailoring Workshops in Bamenda: Implications for Situated Learning - Angu, Nji Roland; Chu, Ambei Moses (Journal of Education and Training, 2023)
This study aimed at investigating situated learning and adolescents’ acquisition of social and cognitive skills in Bamenda in the North West Region of Cameroon. In this regard the researchers sought to provide answers to two important research questions namely: 1) How does modeling influence the acquisition of Social and Cognitive Skills in Tailoring Workshops in Bamenda?; 2) How does coaching influence the acquisition of Social and Cognitive Skills in Tailoring Workshops in Bamenda? The study anchored on three theories which are: Lave and Wenger’s (1991) situated Learning theory, Brown, Allan Collins and Paul Duguid’s (1989) Situated learning cognition and Vygotsky’s (1978) sociocultural perspective of learning. A concurrent nested mixed method design with the help of questionnaire and interviews was used for data collection from some 20 adolescent apprentices learning their trade at tailoring workshops in Bamenda. Findings of the study revealed that modeling influences adolescents’ acquisition of social and cognitive skills. It was also revealed that coaching had a significant influence on the acquisition of social and cognitive skills among adolescent apprentices. A number of recommendations were made to masters/expert tailors, apprentices and the government. As far as master/expert tailors are concerned, they should understand that learning within such an informal context does not always require direct instruction but that it is usually accidental. In this regard, the onus is on them to ensure that they demonstrate clearly the tasks they would eventually expect the novice apprentices to perform so that they can keenly pay attention, observe and eventually perform to the best of their abilities.